Quy tắc về các quá trình và sự biến đổi âm vị học - Võ, Đại Quang (Đại học Quốc gia Hà Nội, 2014)
Phonological processes and alternations in natuaral language can be explicitly represented in phonological rules. This article is focused on providing readers With basic knowledge, via such sets of rules or comments, of pronuncaiation-rolatocl phenomena observable in natural language such as deletion, assimilation, metathesis, reduplication, ... The phonological rules mentioned in this article can be viewed as ail understanding of how the deep structure of language' is to be linked with the surface structure. What we need now is an insight into the nature of phonological structures that function as environment for the operation of* phonological rules.